2017
DOI: 10.1103/physrevaccelbeams.20.061002
|View full text |Cite
|
Sign up to set email alerts
|

LHC optics commissioning: A journey towards 1% optics control

Abstract: Since 2015 the LHC has been operating at 6.5 TeV. In 2016 the β-functions at the interaction points of ATLAS and CMS were squeezed to 0.4 m. This is below the design β Ã ¼ 0.55 m at 7 TeV, and has been instrumental to surpass the design luminosity of 10 34 cm −2 s −1. Achieving a lower than nominal β Ã has been possible thanks to the extraordinary performance of the LHC, in which the control of the optics has played a fundamental role. Even though the β-beating for the virgin machine was above 100%, correction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 15 publications
1
43
0
Order By: Relevance
“…Note that a 11 ¼ −a 22 such that a 11 þ a 22 ¼ 0 in Eq. (9). We know that the trace of T new is also equal to 2 cosð2πðQ þ ΔQÞÞ.…”
Section: A Tune Shift From Modulation Of a Quadrupole Magnetmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that a 11 ¼ −a 22 such that a 11 þ a 22 ¼ 0 in Eq. (9). We know that the trace of T new is also equal to 2 cosð2πðQ þ ΔQÞÞ.…”
Section: A Tune Shift From Modulation Of a Quadrupole Magnetmentioning
confidence: 99%
“…K modulation directly measures the average β function at a modulated quadrupole by measuring the corresponding tune shift. As a result K modulation is slow for global measurements, but can be used for measuring β Ã and has been used to do so in other machines with uncertainty below 1% [8,9]. However, it has been shown that the uncertainty of β Ã measurements using K modulation grows significantly for small values of β Ã [10], raising the question whether K modulation will give accurate measurements in SuperKEKB.…”
Section: Introductionmentioning
confidence: 99%
“…For the crossing plane, it is assumed that the longitudinal bunch shape is taken into account up to a residual error of 5 % as described in the previous section. 5% 5% β * (optics uncertainty) [12] 3% 3% head-on beam-beam kick [19,20] 2% 2% dynamic β * (beam-beam) [20] 2% 2% transverse distribution [15] 5% 5% crossing angle -5% longitudinal distribution -5% combined error 9.6 % 11.9%…”
Section: Systematic Errorsmentioning
confidence: 99%
“…β-beating in the machine to the 2% level and the r.m.s. β Ã -beating down to the 1% level [1][2][3]. However, the continuous effort to reduce the beam sizes at the interaction points is starting to bring up the limitations of current optics measurements and correction methods.…”
Section: Introductionmentioning
confidence: 99%